Peranan Partai Politik Islam Dalam Pelaksanaan Pemilihan Kepala Daerah Serentak di Indonesia - Sri Warjiyati (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
The Islamic Political Parties in support of simultaneous Regional Head Elections in Indonesia have proven to contribute significantly to a very pluralistic national political system. Increasing the capacity and performance of Islamic political parties directly influences the quality of democracy and the performance of the political system in Indonesia, so that the role of Islamic Political Parties needs to be improved, both in capacity, quality and performance in order to realize the quality of democracy in Indonesia. The birth of Islamic parties in Indonesia today has added to the treasures of democracy in Indonesia, this birth phenomenon is thought to be a manifestation of the re-presence of Islamic political power. The quality of democracy can be influenced one of them through the implementation of simultaneous regional head elections in 2018 which are carried out in a constitutional, peaceful, honest and fair manner. The quality of democracy is also determined by the existence of democratic institutions, actors of democracy, actors' relations with institutions, public issues, and the capacity and strategy of democratic actors in linking between political party platforms that carry candidates with issues of public interest. The success of the substance of the implementation of the Regional Head Election simultaneously can be measured from the effectiveness of the system